Representasi Hero Perempuan dalam Film The Hunger Games (Analisis Semiotika dalam Film The Hunger Games) Representation Hero of Women in The Hunger Games (Semiotic Analysis in The Hunger Games) - Eva Fitriani (ILKOM 15 UMY 188, 2015)
*188